Analysis of ASN Planning for The United Nations and Political Agency of Regency Karawang - Sri Maharani; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
This research aims to explain how ASN plans and analyzes the planning strategies used so that job vacancies do not occur. The research approach uses qualitative. This locus is located on Jalan A. Yani By Pass No. 23, Karawang Regency, West Java. The informants in this research were the head of the civil service, the secretariat, the national insight analysis, personnel manager. Data collection is through primary data obtained from interviews, observations, and documentation, and secondary data obtained through library research. Then the data is analyzed using content analysis. The results of the research show that human resource planning at the National Unity and Political Agency has not been implemented well, requiring a planning process for the number of employees, employee recruitment, resources used, work standards, and quality improvement. The priority of managing the number of employees being planned by prioritizing the employee recruitment process through internal sources rather than external sources, to simplify ASN planning. The strategy to overcome this problem focuses on recruitment planning, employee development, and compensation strategies. In this way, organizations can increase the effectiveness of ASN planning, reduce long-term vacancies, and ensure smooth operations and optimal performance.